Analisis Prosedur Penerimaan kas pada PT Bank Central Asia, Tbk Kantor Cabang Utama Pematangsiantar - Eve Ida Malau; Eka septiana parapat; Debora Silvia Hutagalung (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2021)
The purpose of this study was to determine the accounting procedures for cash receipts at PT Bank Central Asia, Tbk Pematangsiantar Main Branch Office. The function of banking is to collect funds from the public in the form of deposits and channel them back to the public in the form of loans/credits. Funds from the public are a source of cash receipts for banks, for example opening accounts, cash deposits and deposits. Cash that goes into the bank must be guarded so that there is no misappropriation. For this reason, a good cash receipts accounting system is needed. The elements needed in the accounting system are documents, records and procedures related to the cash receipts accounting system. The data collection technique used is the interview method and direct observation to the field. The data collected will be analyzed directly by the author as an analytical tool. The analytical technique used by the author is a qualitative analysis technique where the author will conduct an analysis based on the facts found in the field. The results of this study are in the form of a description or analysis of cash receipts accounting procedures.